Catalytic combustion of soot over Cu, Mn substitution CeZrO2-δ nanocomposites catalysts prepared by self-propagating high-temperature synthesis method. (2nd November 2018) - Guan, Bin; Lin, He; Zhan, Reggie; Huang, Zhen
Graphical abstract: Highlights: SHS method is adopted to prepare the nanocomposites catalysts to promote soot combustion. Cu and Mn substitution has a great influence to soot combustion activity. Mn0.09 Cu0.81 Ce0.05 Zr0.05 O2- δ shows the best low temperature soot combustion performance. Active oxygen species and NO2 promote the soot combustion reaction. Nitrite and nitrate species may be the key intermediates of soot combustion. Abstract: This study concentrates on improving the low temperature performance of CDPF catalysts. The self-propagating high temperature combustion synthesis method was applied to synthesize a series of CeZrO2- δ, CuCeZrO2- δ, and MnCuCeZrO2- δ catalysts, which were coated on DPF substrate. The performance of the catalysts was fully investigated by the soot temperature programmed combustion, which showed that these catalysts with nanometer size have a high catalytic activity of soot combustion at low temperatures. Compared with Ce0.05 Zr0.05 O2- δ, Cu0.9 Ce0.05 Zr0.05 O2- δ and Mn0.09 Cu0.81 Ce0.05 Zr0.05 O2- δ showed excellent low temperature soot oxidation activities and much higher CO2 selectivity. BET, XRD, TEM, and XPS were employed to characterize the structural and physical-chemical properties of catalysts. The XRD results indicated that catalysts with 90% Cu possess evenly distributed crystalline grains and small particle size, which is responsible for its excellent oxidation activity by providing more active sites as well as forming good connection between the catalyst and soot. The XPS results demonstrated that the Cu x + has a significant association with the formation of NO2, thus promoting the soot oxidation, and that the synergetic effect between Cu x + and Mn x + contributes most to the improvement of the catalytic activity. The partial substitution with Mn could enhance the chemisorbed oxygen, which further improved NO oxidation and CO2 selectivity. Furthermore, the soot combustion reaction mechanism was examined with in situ DRIFTS. The results exhibited that the active sites of Cu0.9 Ce0.05 Zr0.05 O2- δ and Mn0.09 Cu0.81 Ce0.05 Zr0.05 O2- δ could generate more reactive oxygen for NO oxidation and that the uniformly dispersed Cu x + and Mn x + in Ce lattice could adsorb NO2 to form nitrite and nitrates, which behaved as a carrier of NO2 and transported it around the surface of soot, thus facilitating the soot combustion, especially at low temperatures.